2011
DOI: 10.1369/jhc.2010.956644
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of CD13 in Vessels of Inflammatory and Neoplastic Tissues

Abstract: Aminopeptidase-N (CD13) is an important target of tumor vasculature-targeting drugs. The authors investigated its expression by immunohistochemistry with three anti-CD13 monoclonal antibodies (WM15, 3D8, and BF10) in normal and pathological human tissues, including 58 normal, 32 inflammatory, and 149 tumor tissue specimens. The three antibodies stained vessels in most neoplastic tissues, interestingly with different patterns. As a matter of fact, WM15 stained almost all intratumor and peritumor capillaries and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 59 publications
3
29
1
Order By: Relevance
“…We have previously reported that APN is expressed in tumor blood vessels and is necessary for pathological angiogenesis (15,18,19,23), a function also confirmed by others (8)(9)(10)(11)(12)(13)(14). Reduction in angiogenesis likely accounts for the tumor growth defect resulting from enzyme inactivation.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…We have previously reported that APN is expressed in tumor blood vessels and is necessary for pathological angiogenesis (15,18,19,23), a function also confirmed by others (8)(9)(10)(11)(12)(13)(14). Reduction in angiogenesis likely accounts for the tumor growth defect resulting from enzyme inactivation.…”
Section: Discussionsupporting
confidence: 68%
“…A body of indirect evidence suggests a role for APN in regulating these aspects of tumor progression. Indeed, APN is expressed by both cancer cells and nonmalignant cells such as environmental vascular endothelial cells, neutrophils, and stromal cells (8,14), but it remains unclear where and how APN acts to regulate tumor angiogenesis.We recently generated APN-null mice and found them to have impaired neovascularization in response to hypoxia or growth factor stimulation in the absence of tumor cells (23). We reasoned that the APN-null mouse combined with syngeneic tumor allografts would provide an ideal model system to sort out the roles of tumor and alternative sources of APN in tumor growth and metastasis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This vein also expresses ACE [2,15]. The ectopeptidase APN is present in the vascular smooth muscle cells of the umbilical artery [3,4] and at least in the endothelium of the umbilical vein [16,17].…”
mentioning
confidence: 99%